Reward, risk and response in Australian cooperative research centres. (2nd December 2009) - Turpin, Tim; Garrett-Jones, Sam
Cooperative research centres are a well-established organisational embodiment of the 'triple helix'. As complex inter-organisational structures they are subject to diverse management strategies. The imperatives that drive their strategic plans and their impact on partner organisations and the careers of the scientists who work within them are not well understood. We examine 370 participants' experience in Australian cooperative research centres and consider their effect on personnel and organisations in the public research system. We propose that a necessary part of management strategies is the negotiation and reconciliation of risk and reward for partner organisations and careers of participating scientists. Achieving a sustainable strategy carries implications for change within the partner organisations and for the endurance of CRCs as organisational arrangements. These emergent triple helix structures can be harbingers of change not just for the alternative institutional structures they present and the partner organisations, but also for the careers of scientists.